Economic evaluation of different routes of surgery for the management of endometrial cancer: a retrospective cohort study. Issue 5 (13th May 2021) - Moss, Esther L; Morgan, George; Martin, Antony; Sarhanis, Panos; Ind, Thomas
Abstract : Objectives: The benefits of minimally invasive surgery (MIS) for endometrial carcinoma (EC) are well established although the financial impact of robotic-assisted hysterectomy (RH) compared with laparoscopic hysterectomy (LH) is disputed. Design: Retrospective cohort study. Setting: English National Health Service hospitals 2011–2017/2018. Participants: 35 304 women having a hysterectomy for EC identified from Hospital Episode Statistics. Primary and secondary outcome measures: The primary outcome was the association between route of surgery on cost at intervention, 30, 90 and 365 days for women undergoing an open hysterectomy (OH) or MIS (LH/RH) for EC in England. The average marginal effect was calculated to compare RH versus OH and RH versus LH which adjusted for any differences in the characteristics of the surgical approaches. Secondary outcomes were to analyse costing data for each surgical approach by age, Charlson Comorbidity Index (CCI) and hospital MIS rate classification. Results: A total of 35 304 procedures were performed, 20 405 (57.8%) were MIS (LH: 18 604 and RH: 1801), 14 291 (40.5%) OH. Mean cost for LH was significantly less than RH, whereas RH was significantly less than OH at intervention, 30, 90 and 365 days (p<0.001). Over time, patients who underwent RH had increasing CCI scores and by the 2015/2016 year had a higher average CCI than LH. Comparing the cost of LH and RH against CCI score identified that the costs closely reflected the patients' CCI. Increasing disparity was also seen between the MIS and OH costs with rising age. When exploring the association between provider volume, MIS rate and surgical costs, there was an association with the higher the MIS rate the lower the average cost. Conclusions: Further research is needed to investigate costs in matched patient cohorts to determine the optimum surgical modality in different populations.